Where does Maisy live? - Cousins , Lucy (Someville : Candlewick Press, 2010)
In "Where Does Maisy Live?" by Lucy Cousins, young readers follow Maisy Mouse as she gives them a tour of her home. The book introduces various rooms in Maisy's house, such as the living room, bedroom, and kitchen. Through simple text and colorful illustrations, children learn about Maisy$1 (Bs daily activities and the different parts of a house, making it a fun and engaging way for them to understand and appreciate their own living spaces.s
Simple Text: Bright and Colorful Illustrations Interactive Elements
Keywords: Board books